Evolución histórica de los autómatas educativos - Satán Guanoluisa, Maritza Alexandra (2024)
Although computing has a wide range of uses, historical aspects are rarely studied. As a result, the goal of this work was to disseminate the historical evolution of educational automata via video microcapsules that will allow readers to learn about the information published on the social networks of the Pedagogy of Experimental Sciences career in a concise and entertaining manner. Computing. This project's methodology followed a technical design, with descriptive and applied research. Five instructional video microcapsules were created, covering topics such as automata introduction, historical evolution, generalities of educational automata, educational automata functioning, and educational automata creation. It is advised that teachers explore the usage of automata for educational purposes because with creativity they can be useful in different areas of knowledge.